SYSTEMATIC LITERATURE REVIEW (SLR) : SERTIFIKASI DAN PERMASALAHANNYA - Qurrotun Nada, Laila; Ulia Pratiwi; Yahdi Rauza; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Character education in schools is education that includes values, manners, morals and also manners which have the aim of developing character values and the ability of all school members to make good or bad decisions, to be role models, to be able to maintain good things and Good. develop goodness in life. everyday life. Intellectual intelligence without good character and personality is useless. This study aims to examine literature reviews related to character education in elementary schools. The research method uses the SLR (Systematic Literature Review) method. Data collection was obtained by documenting related articles in similar research. The articles obtained and used in this study as many as 7 national journal articles can be obtained from the Google Scholar database using the publish or perish application. Based on research, in this era of globalization, a person's high morale is also one of the keys to success in building connections in the social world.